The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/diagnostics12020406
|View full text |Cite
|
Sign up to set email alerts
|

A Cytological Review of Follicular Dendritic Cell-Derived Tumors with Emphasis on Follicular Dendritic Cell Sarcoma and Unicentric Castleman Disease

Abstract: Follicular dendritic cells (FDCs) are antigen-presenting cells located in the germinal centers of the lymph nodes. Among the few tumors showing FDC differentiation are follicular dendritic cell sarcoma (FDCS) and Castleman disease (CD), more precisely the unicentric hyaline vascular (HV) variant. Both are relatively rare tumors, and the diagnostic cytological experience is limited to descriptions of isolated cases or small series. The purpose of this review is to bring together all the available cytological pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
(150 reference statements)
0
8
0
Order By: Relevance
“…16 The cytomorphologic features closely resemble those on histology, with large, epithelioid and oval to spindly neoplastic cells that have indistinct cell borders, nuclear grooves, and pseudoinclusions alongside a second population of lymphocytes and plasma cells. 16 The tumor cells are characteristically positive for CD21, CD35, and CD23, with positivity rates of 85%, 55%, and 31.7% respectively. 3 Therefore, a panel of these stains is recommended to help make the diagnosis.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…16 The cytomorphologic features closely resemble those on histology, with large, epithelioid and oval to spindly neoplastic cells that have indistinct cell borders, nuclear grooves, and pseudoinclusions alongside a second population of lymphocytes and plasma cells. 16 The tumor cells are characteristically positive for CD21, CD35, and CD23, with positivity rates of 85%, 55%, and 31.7% respectively. 3 Therefore, a panel of these stains is recommended to help make the diagnosis.…”
Section: Discussionmentioning
confidence: 65%
“…16 On the nice review by Jiménez-Heffernan, 26 cases of FDCS diagnosed on cytology were reported on the literature, most of them from lymph nodes. 16 The cytomorphologic features closely resemble those on histology, with large, epithelioid and oval to spindly neoplastic cells that have indistinct cell borders, nuclear grooves, and pseudoinclusions alongside a second population of lymphocytes and plasma cells. 16 The tumor cells are characteristically positive for CD21, CD35, and CD23, with positivity rates of 85%, 55%, and 31.7% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abdominal UCD is always mistaken for lymphatic tuberculosis, stromal tumor, neuroendocrine tumor, adrenal adenoma and even accessory spleen, [4] leading to wrong management strategies. Nevertheless, UCD is still with a risk of progression to lymphoma or follicular dendritic cell sarcoma [5,6] , though it is convinced to be an inert disease with a good prognosis. Thus, it is of great importance to make an exact diagnosis at the first visit.…”
mentioning
confidence: 99%